Impact of immersive virtual reality simulations for changing knowledge, attitudes, and behaviors. (October 2021) - Gillespie, Gordon Lee; Farra, Sharon; Regan, Saundra L.; Brammer, Susan V.
Abstract: Background: Virtual reality has promise as a training method within the affective domain, but investigation is still needed for intention to change behaviors based on social determinants of health. Objective: The objective of this study was to describe the self-reported changes in knowledge and/or attitudes and planned behavior changes by healthcare workers for their future care of persons with challenges to their social determinants of health following completion of a first-person virtual reality experience. Design: A descriptive qualitative design was used. Settings: This study was conducted in clinics and private practice settings in Ohio (United States). Participants: This study was conducted with 206 healthcare workers. Methods: Participants completed a virtual reality simulation followed by qualitative, open-ended questions about changes to their knowledge, attitudes, and behaviors. Responses were analyzed using a content analysis method. Results: Four overarching themes were derived from the qualitative data: (1) Acknowledgement of Social Determinants of Health, (2) An Improved Provider Experience for Patients, (3) Patient as a Person with Complex Needs, and (4) The Learning Experience. Conclusion: Findings suggest virtual reality has strong merits for impacting affective domain of learning demonstrated by increased empathy. Virtual reality along with increased empathy also helps improve attitudes and behaviors for the betterment of patients.